2023
DOI: 10.1371/journal.pone.0283876
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, attitudes, and behaviors of asthma patients towards the use of short-acting β2-agonists: A systematic review

Abstract: Background Short-acting β2-agonists (SABA), the most potent and rapid-acting relievers are commonly used to provide quick relief of asthma symptoms. However, there is an increasing concern regarding the misuse of SABA medicines. Objective This qualitative systematic review aims to determine, evaluate, and summarize the perceptions, attitudes, and behaviors towards the use of SABA from the patients’ perspectives. Methods The databases searched included PubMed, Scopus, PsycINFO, CINAHL, and Cochrane database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In other countries, physician over-prescribing behaviours have been attributed to variability in thresholds for acceptable SABA use, questioning of the risk of morbidity and mortality with high SABA use, and a consideration that asthma guidelines are too ‘stringent’ [ 12 ]. Overuse of SABA by patients has been linked to a lack of knowledge that frequent usage would worsen asthma control, and strong psychological links to use of SABA, due to immediate relieving effects [ 22 ]. SABA overuse in Australia may also reflect specific peculiarities of the healthcare system and reimbursement practices [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, physician over-prescribing behaviours have been attributed to variability in thresholds for acceptable SABA use, questioning of the risk of morbidity and mortality with high SABA use, and a consideration that asthma guidelines are too ‘stringent’ [ 12 ]. Overuse of SABA by patients has been linked to a lack of knowledge that frequent usage would worsen asthma control, and strong psychological links to use of SABA, due to immediate relieving effects [ 22 ]. SABA overuse in Australia may also reflect specific peculiarities of the healthcare system and reimbursement practices [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies that were included in the review, SABA overuse was associated with underuse of preventers [ 51 , 52 ]. The results of several studies included in this review indicated that asthma patients may tend to over-rely on SABA due to inability to cope with the situation, social challenges, fear of symptoms, and the belief that they cannot manage their condition without SABA inhalers [ 1 , 17 , 53 , 54 ]. These results match expert opinion, or results of research not included in this review (i.e., studies that did not capture prevalence of SABA OTC use or overuse) [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The statistical data were included, where available, to indicate the magnitude of the key findings, it was not used in the data synthesis process. As a result, handling of any missing summary statistics was not needed in this systematic review [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations